Stratifying Neurological Severity in Acute Ischemic Stroke: The Independent and Combined Prognostic Value of Admission D-Dimer and High-Sensitivity C-Reactive Protein - Syufriyadi DS; Zulfikar Lubis; Chairil Amin Batubara (HM Publisher, 2025)
Background: Early risk stratification in acute ischemic stroke (AIS) is critical for optimizing patient management. The roles of inflammation and thrombosis in stroke pathophysiology suggest that high-sensitivity C-reactive protein (hs-CRP) and D-Dimer may serve as valuable prognostic biomarkers. This study aimed to evaluate the independent and combined value of admission D-Dimer and hs-CRP levels for predicting neurological severity in AIS patients. Methods: We conducted a prospective, cross-sectional study at Haji Adam Malik General Hospital, Medan, Indonesia, involving 60 consecutive AIS patients. Neurological severity was assessed upon admission using the National Institutes of Health Stroke Scale (NIHSS), with patients categorized into moderate (NIHSS 5-18) and severe (NIHSS >18) groups. Plasma D-Dimer and serum hs-CRP levels were quantified. Statistical analyses included the Mann-Whitney U test, Spearman's correlation, Receiver Operating Characteristic (ROC) curve analysis, and multivariate logistic regression to determine the independent predictive value of the biomarkers. Results: Of the 60 patients, 31 (51.7%) were classified as having severe stroke. Both D-Dimer and hs-CRP levels were significantly higher in the severe group compared to the moderate group (D-Dimer: median 3220 ng/mL vs. 670 ng/mL, P<0.001; hs-CRP: median 5.6 mg/dL vs. 0.9 mg/dL, P<0.001). ROC analysis demonstrated strong predictive performance for severe stroke, with an Area Under the Curve (AUC) of 0.89 (95% CI: 0.81-0.97) for D-Dimer and 0.83 (95% CI: 0.72-0.94) for hs-CRP. A combined model incorporating both biomarkers yielded a superior AUC of 0.92 (95% CI: 0.85-0.99). In multivariate logistic regression, both elevated D-Dimer (Odds Ratio [OR]: 6.8, 95% CI: 2.1-22.5, P=0.001) and hs-CRP (OR: 4.5, 95% CI: 1.5-13.8, P=0.008) remained independent predictors of severe stroke after adjusting for age and gender. Conclusion: Admission levels of D-Dimer and hs-CRP are powerful, independent prognostic markers for neurological severity in patients with acute ischemic stroke. Their use, particularly in combination, could enhance early risk stratification and guide clinical decision-making.